1980
DOI: 10.1016/s0022-5347(17)55980-7
|View full text |Cite
|
Sign up to set email alerts
|

Flow Cytometry in Bladder Cancer Detection and Evaluation Using Acridine Orange Metachromatic Nucleic Acid Staining of Irrigation Cytology Specimens

Abstract: A new technique for simultaneous multiparameter deoxyribonucleic acid, ribonucleic acid and nuclear size measurements by flow cytometry was applied to the examination of bladder irrigation cytology specimens from 107 urologic patients. The cell samples from patients with bladder carcinoma could be distinguished from normal by 2 features: 1) an increase in the proportion of bladder epithelial cells with more than diploid deoxyribonucleic acid and 2) aneuploid cell peaks. These criteria identified 12 of 13 cases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0
1

Year Published

1980
1980
1998
1998

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 79 publications
(21 citation statements)
references
References 5 publications
2
18
0
1
Order By: Relevance
“…A total rate of diagnosis of 81 % was achieved in a study by Collste et al [20]. This consists of 35% proven aneu ploidies (which is comparable to our own results), 5% with a CV of greater than 10% (an exclusion criterion in our investigation), 18% with a clear tetraploid peak as well as 23% with a proliferative rateof>l 5% S + G2 M phase.…”
Section: Sensitivitysupporting
confidence: 87%
See 2 more Smart Citations
“…A total rate of diagnosis of 81 % was achieved in a study by Collste et al [20]. This consists of 35% proven aneu ploidies (which is comparable to our own results), 5% with a CV of greater than 10% (an exclusion criterion in our investigation), 18% with a clear tetraploid peak as well as 23% with a proliferative rateof>l 5% S + G2 M phase.…”
Section: Sensitivitysupporting
confidence: 87%
“…Boileau et al [11] made the criticism that aneuploidy rates in previous studies by other authors [20] are created against nomenclature. They already see 'asymmetric peaks of Goi or simply just broadened CV' as proof of aneuploidy, thereby increasing sensitivity for well and moderately differentiated tumors without examining a control group of tumor-free patients by the same criteria.…”
Section: Limits Oj'aneuploidy Recognitionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some investigators have addressed this problem. Collste et al [22]stained urothelial cells with acridine orange and reported that granulocytes could be distinguished from urothelial cells by lower DNA content, as well as by an increased nuclear size. Lymphocytes and monocytes, however, cannot be excluded by this technique.…”
Section: Discussionmentioning
confidence: 99%
“…So far, some investigators have addressed this problem. Collste et al [13], staining urothelial cells with acridine orange, re ported that granulocytes could be distinguished from transitional cells by their low DNA, as well as by an increased nuclear size due to the presence of unfolded nuclei. Lymphocytes and monocytes, however, cannot be excluded by this technique.…”
Section: Discussionmentioning
confidence: 99%